USING IT GOVERNANCE BALANCED SCORECARD AND IMPORTANCE-PERFORMANCE ANALYSIS FOR DEVELOPING IT GOVERNANCE IN HIGHER EDUCATION INSTITUTION (AN EMPIRICAL STUDY IN EAST JAVA, INDONESIA) - Khristianto, Wheny (Universitas Muhammadiyah Jember, 2020)
The purpose of this paper is to investigate the validity of the higher education academic staffs in IT governance studies and the future improvement for IT governance and controls. This research used a quantitative survey to identify the current state of IT governance for five higher education institutions in East Java, Indonesia. The questionnaires were distributed to post-graduate student as IT executives in their higher education institution. A total of 34 out of 40 post academic staffs completed the questionnaire, representing a response rate of 85 percent. This study found that attributes for deliver value (V2), attainment and retain people with key competencies (V6), capture knowledge to improve performance (V10), stakeholder satisfaction (V11), reach economies of scale (V17) , deliver successul IT project (V19), understand business unit strategies (V20), and understand emerging technologies (V22) show no significant difference (p 0.05) between mean interests and performance. In addition to these, other 15 attributes show significant differences in the t-test in the negative direction. This points to the fact that actual control of IT governance in colleges is monitored less than expected. Therefore, five higher education institutions in East Java should pay more attention to the identified attributes important to balance the gap between the importance and performance of these attributes.Â